Determinación de úlcera corneal en caninos determinado por el método de la fluoresceína en la ciudad de Machala - Ochoa Valdiviezo, María Daniela (2012)
In the city of Machala was made a study of corneal ulcer diagnosed by fluorescein method. Objectives of this study were: 1. To determine the presence of ulcerative keratitis in animals suspected diagnosis through a sample of fluorescein in the canine population in the City Veterinary Clinics of Machala. 2. Set the interaction of positive cases by race, sex, age and origin of the caseload. 150 cases were treated in different Veterinary Clinics, the same that were consistent with eye injuries and diseases found in animals treated with a high incidence of positive cases. By studying the interaction between age and positive cases found a high percentage of positive animals from 6 to 12 months of age. Among animals pure and mixed there was a greater percentage of the pure corneal ulcer in the mestizos, the races that increased presence of pathology was presented Shih Tzu and Poodle. Likewise, the relationship between the sexes and the positive cases there was no numerical difference.